(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Physical training of young athletes is considered one of the most important components of sports training and is understood as a process aimed at comprehensive development of the body, strengthening of health, improvement of physical abilities and creation of a solid functional base for all other types of training.